Effects of Smoking Status on Device Survival Among Individuals Undergoing Artificial Urinary Sphincter Placement. Issue 5 (September 2018) - Godwin, Christina A.; Linder, Brian J.; Rivera, Marcelino E.; Ziegelmann, Matthew J.; Elliott, Daniel S.
Smoking is an established risk factor for wound complications. There is limited data on the impact of smoking on artificial urinary sphincter (AUS) outcomes. Thus, the aim of this study was to assess AUS device survival outcomes based on smoking status. From 1985 to 2014, 1, 270 patients underwent AUS placement with 728 having smoking status available for review. Smoking status was categorized as never, prior, and active smokers. Kaplan−Meier analysis was performed to evaluate differences in survival, including overall device and erosion/infection−free survival. Hazard regression analysis was utilized to determine the association between smoking and device outcomes. Of the 728 patients in the study, 401 had a history of smoking with 41 active smokers and 360 never smokers at the time of AUS implant. When compared with nonsmokers, past smokers had a higher rate of hypertension and prior transient ischemic attack. Clinical comorbidities were similar between nonsmokers and active smokers. On univariate analysis, patient age, history of transient ischemic attack, diabetes, and coronary artery disease were significantly associated with infection/erosion rate, but prior or active smoking statuses were not. Likewise, when comparing smokers (past or active) with lifelong nonsmokers, there was no significant difference in 1- and 5-year overall device survival. There was no evidence for adverse AUS outcomes in current or past smokers compared with nonsmokers. Given the established risk of perioperative complications secondary to smoking, the recommendation should still be to counsel patients to quit prior to undergoing AUS placement. External validation of these findings is needed.